Evidence for water deficit-induced mass increases of raffinose family oligosaccharides (RFOs) in the leaves of three Craterostigma resurrection plant species - Egert, Aurelie; Eicher, Barbara; Keller, Felix; Peters, Shaun (Frontiers in Physiology, 2015)
The leaves of the resurrection plant Craterostigma plantagineum accumulate sucrose during dehydration, via a conversion from the unusual C8 ketose-sugar 2-octulose. However, raffinose family oligosaccharides (RFOs) have been shown to be major photosynthetic products in this plant. The tetrasaccharide stachyose is the major phloem mobile carbohydrate and is used as a carbon store in roots. It has been suggested that this carbon store is remobilized during rehydration, presumably for cellular repair processes. We examined the effects of water deficit on the leaf water-soluble carbohydrate profiles of three Craterostigma species. Apart from the classical 2-octulose to sucrose interconversion, there was a strong water deficit-associated mass increase of RFOs up to the pentasaccharide verbascose. However, the activities of three dedicated RFO biosynthetic enzymes (raffinose, stachyose and verbascose synthase) could not be correlated with RFO accumulation, suggesting that biosynthetic enzymes activities measured in the early stages of water-deficit was sufficient to synthesize enough Gol and lead to RFO accumulation in the leaves. Our findings are suggestive of RFOs providing additional carbohydrate-based stress protection to the leaves of these plants during the desiccated state.